KINERJA PEGAWAI DINAS PENDIDIKAN KOTA BATU: GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI - Harnani, Sri; Kurniawati, Rif Susi (Manajemen & Bisnis Jurnal, 2021)
The objective of the study is to analyze and explain the influence of leadership style on organizational commitment, the influence of leadership style on employee performance and the influence of leadership style on employee performance. Leadership on employee performance is influenced by organizational commitment style. The study population included 5 employees of the Batu City Office of Education. The results of the study explain that leadership style directly affects employee performance and organizational commitment and organizational commitment can influence leadership style on employee performance.